VD_FINDINFO Décision / 2014 / 227 vom 4. Dezember 2013 - VD Tribunal cantonal (2013)
DEMANDE ADRESSÉE À L'AUTORITÉ, RÉCUSATION, DÉCISION D'IRRECEVABILITÉ | 310 CPP (CH), 383 al. 1 CPP (CH), 56 let. f CPP (CH)